(untitled) (Faridpur Medical College Journal, 2020)
Adverse events due to platelet pheresis are not unheard of citrate related reactions being the most common. Most of these events are mild and self limiting. The current study describes adverse events in platelet pheresis using modern apheresis systems. This prospective study included 1455 platelet pheresis procedures done from July 2016 to December 2017. Procedures were performed on Hemonetics MCS+, Trima Accel and Cobe spectra cell separators. The endpoint of each procedure was a yield of 3 × 1011 platelets (PLTs) per unit. Donor adverse reaction if any was managed, reported, and documented. The median age of donors was 31 years with male to female ratio of 13:1. The median body surface area and body mass index were 1.64 m2 and 22.4 kg/m2, respectively. The mean PLT count of donors was 199.8 × 103/uL with a mean hemoglobin value of 13.6 g/dl. ACD infusion was significantly more in the Hemonetics MCS+, (P< 0.01). Donation time was least with the Trima compared to Hemonetics MCS+ (P< 0.01) and Cobe (P< 0.001). Total whole blood volume processed was higher in Hemonetics MCS+, (P< 0.01). Paresthesia due to citrate toxicity was the most common adverse reaction (65.3%), and vascular injury was observed in only five donors. The overall incidence of adverse reaction was 3.4%. Serious adverse events were not observed. The modern generation apheresis machines are more donors friendly and cause less adverse reactions compared to the older versions. Good donor screening, optimized donor physiognomic and hematological values and skilled operators are the key factors in reaction reduction by apheresis. Faridpur Med. Coll. J. Jan 2019;14(1): 27-30